Imaging-defined complete response to immune checkpoint inhibitors predicts durable survival in advanced hepatocellular carcinoma - Shao, Yongjie; Yuan, Junhui; Liu, Yanwei; Wang, Feng (Frontiers in Oncology, 2026)
BackgroundImmune checkpoint inhibitors (ICIs) have revolutionized advanced hepatocellular carcinoma (HCC) treatment, yet complete responses (CRs) remain rare, and their long-term outcomes are poorly characterized. This study evaluates clinical outcomes, pathologic correlates, and optimal management strategies for HCC patients achieving CR to ICI-based therapy.MethodsWe retrospectively analyzed 160 patients with advanced HCC who attained CR (70 by mRECIST; 90 by RECIST v1.1) following ICI therapy at four tertiary centers. Outcomes included recurrence-free survival (RFS), overall survival (OS), and pathologic validation of radiographic CR. Multivariable Cox models identified predictors of RFS.ResultsCRs occurred in 4.8% of treated patients. The cohort demonstrated exceptional survival, with 3-year OS and RFS rates of 86% and 55%, respectively. Among the 8 patients who underwent resection or liver transplantation, 6 (75%) achieved pathologic complete response, 2 in the CR-RECISTv1.1 group and 4 in the CR-mRECIST-only group, supporting imaging validity. Multivariable analysis revealed presence of macrovascular invasion (aHR 2.47, p=0.003) and presence of extrahepatic metastases (aHR 2.00, p=0.011) as independent risk factors for recurrence, while CR by RECIST v1.1 predicted improved RFS (aHR 0.62, p=0.015). Patients continuing ICI ≥6 months post-CR had superior 3-year RFS (81% vs. 55%, p=0.002). Of 11 patients undergoing curative conversion therapy (resection/transplantation/ablation), 92% survived at 3 years with 75% RFS.ConclusionsCR to ICI therapy, though uncommon, correlates with unprecedented survival in advanced HCC, even among high-risk subgroups. mRECIST-defined CR shows strong pathologic concordance, addressing concerns about anti-angiogenic confounders. Extended ICI duration post-CR and selective conversion therapy may optimize outcomes. These findings redefine prognostic paradigms and underscore the need for biomarker-driven strategies to sustain remission.